An EMG-based variable impedance control for elbow exercise: preliminary study. (3rd August 2017) - Kim, Yeoun-Jae; Park, Chang-Kyu; Kim, Kwang Gi
Abstract: As the medical field continues to evolve, the average life expectancy of the people increases. However, due to natural deterioration, the average muscle force of the arm decreases in respect to age. So, there are some needs for the people to exercise his/her body as he/she is getting older. There are many researches about the robotic rehabilitation of the upper limb for patients. However, only a few focus on the system of the upper limb muscle exercise for normal people. So, in this study, an electromyography (EMG)-based variable impedance control method is developed for elbow exercise in normal people. Four EMG sensors were attached to the designated right arm and their average EMG level was controlled by the proposed algorithm during an elbow flexion-extension exercise. A total of twenty nine experiments with 15 subjects were performed to verify the proposed control algorithm with NCCEES, an elbow exercise system developed by the authors for the elbow exercise. The experimental results showed that the proposed control algorithm could control the EMG level in approximately 24.1% percent error during the elbow exercise. However, the proposed control algorithm could not control the EMG level fluctuation which depended on the muscular characteristics of the subject. The effect of training with the proposed algorithm will be future work. Graphical Abstract: